Implementasi Standar Nasional Perpustakaan (SNP 007:2012) Pada Standar Koleksi dan Standar Sarana Prasarana di Perpustakaan SDN Wiyung I / 453 Surabaya - Hendrik Anandra Setiyawan (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2021)
This study discusses the Implementation of National Library Standards (SNP 007:2012) on Collection Standards and Infrastructure Standards in the Library of SDN Wiyung I/453 Surabaya regarding collection standards and infrastructure. The purpose of this study is to describe how the implementation of collection standards and infrastructure facilities in the library of SDN Wiyung I/453 Surabaya. The research method used is descriptive research with a qualitative approach. Based on the results of research that has been researched by the author, it can be concluded that the Library of SDN Wiyung I/453 Surabaya in the collection standard has met the National Library Standard (SNP 007:2012). As for the standard of facilities and infrastructure, some do not meet the National Library Standard (SNP 007:2012) especially for the area of the building/library space which is still 64 m2 but for the facilities, area, and location it is following the National Library Standard (SNP 007:2012). Keywords: Implementation; national library standards; collections; facilities, and infrastructure